CD95 ligand-expressing tumors are rejected in anti-tumor TCR transgenic perforin knockout mice - Behrens, Christian; Arnold, Bernd; Krammer, Peter H. (The journal of immunology, 2001)
CD95 (APO-/Fas) ligand (CD95L) is a member of the TNF family predominantly expressed by activated T and NK cells but also by tumors of diverse cellular origin. CD95L trimerizes surface CD95 expressed by target cells that subsequently undergo apoptosis. The role of the CD95/CD95L system in the down-regulation of an immune response (activation-induced cell death) is established. However, it is so far unclear why tumors express CD95L. To investigate whether tumors use the CD95L to down-regulate an anti-tumor immune response, we established a transgenic (tg) mouse model consisting of 1) apoptosis-resistant tumor cells, designated LKC-CD95L, which express functional CD95L and the model tumor Ag Kb; and 2) perforin knockout (PKO) anti-Kb TCR tg mice. L1210-Fas antisense expressing Kb, crmA, and CD95L (LKC-CD95L) killed CD95+ unrelated tumor targets and Con A-activated splenocytes from anti-Kb TCR tg PKO mice by a CD95L-dependent mechanism in vitro. However, we could not detect any cytotoxic activity against anti-tumor (anti-Kb) T cells in vivo. We also observed reduced growth of LKC-CD95L in nude mice and rapid rejection in anti-Kb TCR tg PKO mice. Because the tumor cells are resistant to CD95L-, TNF-α-, and TNF-related apoptosis-inducing ligand-induced apoptosis and the mice used are perforin-deficient, the involvement of these four cytotoxicity mechanisms in tumor rejection can be excluded. The histological examination of tumors grown in nude mice showed infiltration of LKC-CD95L tumors by neutrophils, whereas L1210-Fas antisense expressing Kb and crmA (LKC) tumor tissue was neutrophil-free. Chemotaxis experiments revealed that CD95L has no direct neutrophil-attractive activity. Therefore, we conclude that LKC-CD95L cells used an indirect mechanism to attract neutrophils that may cause tumor rejection.
Gesehen am 27.04.2021